Effect of bystander initiated cardiopulmonary resuscitation on ventricular fibrillation and survival after witnessed cardiac arrest outside hospital. Issue 5 (November 1994) - Herlitz, J; Ekström, L; Wennerblom, B; Axelsson, A; Bång, A; Holmberg, S
Abstract : OBJECTIVE--To describe the proportion of patients who were discharged from hospital after witnessed cardiac arrest outside hospital in relation to whether a bystander initiated cardiopulmonary resuscitation. PATIENTS--All patients with witnessed cardiac arrest outside hospital before arrival of the ambulance and in whom cardiopulmonary resuscitation was attempted by the emergency medical service in Gothenburg during 1980-92. RESULTS--Cardiopulmonary resuscitation was initiated by a bystander in 18% (303) of 1, 660 cases. In this group 69% had ventricular fibrillation at first recording compared with 51% in the remaining patients (P < 0.001). Among patients in whom cardiopulmonary resuscitation had been initiated by a bystander 25% were discharged alive versus 8% of the remaining patients (P < 0.001). Independent predictors of survival were in order of significance: initial arrhythmia (P < 0.001), interval between collapse and arrival of first ambulance (P < 0.001), cardiopulmonary resuscitation initiated by a bystander (P < 0.001), and age (P < 0.01). Among patients who were admitted to hospital alive 30% of patients in whom cardiopulmonary resuscitation had been initiated by a bystander compared with 58% of remaining patients (P < 0.001) had brain damage and died in hospital. Corresponding figures for death in association with myocardial damage were 18% and 29% respectively (P < 0.01). CONCLUSIONS--Cardiopulmonary resuscitation initiated by a bystander maintains ventricular fibrillation and triples the chance of surviving a cardiac arrest outside hospital. Furthermore, it seems to protect against death in association with brain damage as well as with myocardial damage.